Aquaculture : principles and practices - Pillay, T V R Kutty, M N (BlackWell International, 2005)
"This comprehensive work is an essential purchase for all those studying aquaculture and is a valuable source of reference for all personnel involved in the aquaculture industry, including those working in fish farms, research institutions, teaching posts in universities and commercial establishments such as aquaculture equipment and feed supply companies. Libraries in universities and research establishments will find this book an important addition to their shelves."--Jacket.